ECG changes in rats after prenatal hypoxia and course treatment with modulators NO - Pоpazova, O. О.; Попазова, Олена Олександрівна (Запорізький державний медико-фармацевтичний університет, 2023)
Purpose of the study: to assess the cardioprotective effect of препаратов – модулятров системы NO by the effect on the ECG of 2-month-old rats after prenatal hypoxia.
Keywords: тези доповідей